Perspektif Calon Guru Pendidikan Jasmani Terhadap Pembelajaran Online Selama Pandemi Covid-19 - Victorian, Ahmad Richard; Aryanti, Silvi; Yusfi, Herri; Solahuddin, Soleh; Bayu, Wahyu Indra (Journal of Sport Science and Education, 2021)
Currently, the higher education system is in a continuous process of change. There is a change paradigm in learning that is nowadays being carried out online, or what is commonly known as e-learning. The purpose of this study was to discover college students perspective of e-learning that have been applied. An online survey with a semi-structured questionnaire was conducted on 177 (M: 112; F: 65) college students of the Physical Education, Health and Recreation Departement, Faculty of Teacher Training, Sriwijaya University. The results show that 70.06% of students liked the application of e-learning during the Covid-19 pandemic, but on the next semester, 63.84% of students wanted face-to-face (offline) learning. This is because 67.79% & 69.49% of students stated that there were lack of interaction with lecturers and classmates in the application of e-learning, although 64.41% of students think that the application of e-learning can increase their learning independency. The contradiction in the results of the study shows, only when an extraordinary event (pandemic) occurs, the application of e-learning becomes a priority to do, but if the situation returns to normal, students prefer faceto-face (offline) learning. This is because students are accustomed to practice in the field as a PE teacher candidate.